Sliding member

By forming a Bi-Sb oxide overlay on a sliding member with a Bi and Sb alloy plating coating, the fatigue resistance issues associated with bismuth oxide overlays in engine oil are addressed, resulting in a more durable sliding member.

JP7664256B2Active Publication Date: 2025-04-17TAIHO KOGYO CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022538659
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-22
Filing Date
2021-06-28
Publication Date
2025-04-17
Estimated Expiration
2041-06-28

AI Technical Summary

Technical Problem

Sliding members with bismuth oxide overlays suffer from reduced fatigue resistance due to the brittleness and flaking off of bismuth oxide when used in engine oil, leading to oxidation and increased thickness of bismuth oxide.

Method used

A sliding member with an overlay formed from an alloy plating coating of Bi and Sb, where a Bi-Sb oxide is formed on the surface before use, preventing the formation and growth of bismuth oxide and enhancing fatigue resistance.

Benefits of technology

The Bi-Sb oxide overlay significantly improves fatigue resistance by preventing the flaking off of bismuth oxide and maintaining the integrity of the overlay, even under conditions of engine oil use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007664256000003
    Figure 0007664256000003
  • Figure 0007664256000004
    Figure 0007664256000004
  • Figure 0007664256000005
    Figure 0007664256000005
Patent Text Reader

Abstract

[Problem] To provide a sliding member comprising an overlay capable of realizing good fatigue resistance while preventing peeling between layers. [Solution] A sliding member comprising an overlay formed by a Bi-Sb alloy plating film, wherein a Bi-Sb oxide is formed on the surface of the overlay.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sliding member having an overlay of a Bi-Sb alloy plating film. [Background technology]

[0002] Conventionally, a sliding member having an overlay made of Bi has been known. For example, Patent Document 1 discloses a technique for improving seizure resistance by forming bismuth oxide on the surface of the overlay. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 6087684 Summary of the Invention [Problem to be solved by the invention]

[0004] However, when the sliding member of Patent Document 1 is used in engine oil, oxidation progresses and the thickness of the bismuth oxide increases. Because bismuth oxide is hard and brittle, if a large amount of bismuth oxide is present in the overlay, the bismuth oxide falls off from the overlay during use, resulting in a decrease in fatigue resistance.

[0005] The present invention has been made in consideration of the above problems, and has an object to improve fatigue resistance. [Means for solving the problem]

[0006] In order to achieve the above object, the sliding member is a sliding member having an overlay formed of a Bi-Sb alloy plating film, and the surface of the overlay is provided with , before use Bi-Sb oxide is formed.

[0007] Bi-Sb oxide is more resistant to brittle fracture than bismuth oxide. Furthermore, the presence of Bi-Sb oxide on the surface of the overlay prevents the formation and growth of bismuth oxide. Therefore, the Bi-Sb oxide formed on the surface of the overlay prevents the bismuth oxide from falling off, and improves the fatigue resistance of the sliding member. [Brief description of the drawings]

[0008] [Figure 1] FIG. 2 is a perspective view of a sliding member according to an embodiment of the present invention. [Diagram 2] FIG. [Diagram 3] 1 is a graph showing a fatigue area ratio. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Here, the embodiments of the present invention will be described in the following order. (1-1) Structure of sliding member: (1-2) Manufacturing method of slide member: (2) Experimental results: (3) Other embodiments:

[0010] (1-1) Structure of sliding member: FIG. 1 is a perspective view of a sliding member 1 according to one embodiment of the present invention. The sliding member 1 includes a backing metal 10, a lining 11, and an overlay 12. The sliding member 1 is a metal member having a half-shaped configuration obtained by dividing a hollow cylinder into two equal parts in the diametric direction, and has a semicircular cross section. A plain bearing A is formed by combining two sliding members 1 into a cylindrical shape. The plain bearing A bears a cylindrical mating shaft 2 (a crankshaft of an engine) in a hollow portion formed inside. The outer diameter of the mating shaft 2 is formed slightly smaller than the inner diameter of the plain bearing A. Lubricating oil (engine oil) is supplied to a gap formed between the outer peripheral surface of the mating shaft 2 and the inner peripheral surface of the plain bearing A. At that time, the outer peripheral surface of the mating shaft 2 slides on the inner peripheral surface of the plain bearing A.

[0011] The sliding member 1 has a structure in which a backing metal 10, a lining 11, an intermediate layer 13, and an overlay 12 are laminated in this order from the farthest from the center of curvature. Therefore, the backing metal 10 constitutes the outermost layer of the sliding member 1, and the overlay 12 constitutes the innermost layer of the sliding member 1. The backing metal 10, the lining 11, the intermediate layer 13, and the overlay 12 each have a constant thickness in the circumferential direction. The thickness of the backing metal 10 is, for example, 1.5 mm, the thickness of the lining 11 is, for example, 0.2 mm to 0.3 mm, the thickness of the intermediate layer 13 is, for example, 1.0 to 7.0 μm, and the thickness of the overlay 12 is, for example, 3 to 20 μm. The radius of the surface of the overlay 12 on the side of the center of curvature (the inner diameter of the sliding member 1) is, for example, 55 mm. The width of the plain bearing A is, for example, 19 mm. Hereinafter, the inner side means the side of the center of curvature of the sliding member 1, and the outer side means the side opposite to the center of curvature of the sliding member 1. The inner surface of the overlay 12 constitutes the sliding surface of the mating shaft 2.

[0012] In this embodiment, the backing metal 10 is formed of steel containing, for example, 0.15 mass % C, 0.06 mass % Mn, and the remainder being Fe. Note that the backing metal 10 does not necessarily have to be formed of steel as long as it is made of a material that can support the load from the mating shaft 2 via the lining 11 and the overlay 12.

[0013] The lining 11 is a layer laminated on the inside of the backing metal 10 and constitutes a base layer. In this embodiment, the lining 11 is made of a Cu alloy. The elements contained in the lining 11 are not limited, but an example of the lining 11 being made of a Cu-Bi alloy can be given. Of course, elements other than Cu and Bi may be added, and for example, the lining 11 can be made of a Cu alloy containing 5 mass%, 5 mass%, and 5 mass% of Bi, Sn, and Ni, respectively, with the remainder being Cu. The lining 11 can also be made of a Cu alloy containing 3 mass%, 3 mass% of Bi, and 3 mass% of In, respectively, with the remainder being Cu.

[0014] Furthermore, the lining 11 may be an alloy other than a Cu alloy, for example, an Al alloy. Various elements are assumed to be added to the Al alloy, for example, Sn, Si, Mg, etc. More specifically, the lining 11 may be made of an Al alloy containing, for example, 7 mass% Sn and 3 mass% Si, respectively, with the remainder being Al. The lining 11 may also be made of an Al alloy containing 3 mass% Mg and the remainder being Al.

[0015] Of course, the presence or absence and concentration of these elements are merely examples, and unavoidable impurities may be included. The unavoidable impurities in the lining 11 are Mg, Ti, B, Pb, Cr, etc., and impurities that are mixed in during refining or scrapping are assumed. The content of the unavoidable impurities in the lining 11 is, for example, 0.5 mass% or less in total.

[0016] The intermediate layer 13 may be omitted or may be provided to utilize various functions. For example, in a configuration in which the lining 11 is a Cu alloy, when the intermediate layer 13 containing Ag as a main component is formed between the overlay 12 and the lining 11, the amount of Cu diffusing from the lining 11 to the overlay 12 can be reduced, and the possibility of a decrease in fatigue resistance can be reduced. The intermediate layer containing Ag as a main component may be, for example, pure Ag or Ag-Sn. In the latter case, the concentration of Sn may be, for example, 20 mass %.

[0017] The intermediate layer 13 may be composed of a plurality of layers. For example, in a configuration in which the lining is an Al alloy, a first intermediate layer mainly composed of Cu is formed on the lining 11, and a second intermediate layer mainly composed of Ag is formed between the first intermediate layer and the overlay 12. In these configurations, the first intermediate layer may be composed of pure Cu, for example. The second intermediate layer may be composed of pure Ag or Ag-Sn, for example. In the latter case, the concentration of Sn may be, for example, 20 mass %. Of course, the configuration of the intermediate layer is not limited to these examples, and may be composed of, for example, a first intermediate layer mainly composed of Ag is formed on various linings, and a second intermediate layer mainly composed of Ag-Sn is formed between the first intermediate layer and the overlay 12.

[0018] According to the above configuration, the amount of Cu diffusing from the Cu in the first intermediate layer to the overlay 12 can be reduced by the second intermediate layer mainly composed of Ag, and the possibility of a decrease in fatigue resistance can be reduced. Furthermore, since the first intermediate layer is formed of Cu, the possibility of interlayer peeling occurring between the second intermediate layer and the lining 11 can be reduced. The intermediate layer 13 may contain unavoidable impurities. The content of unavoidable impurities in the intermediate layer 13 is, for example, 0.5 mass % or less in total.

[0019] The overlay 12 is a layer laminated on the inner surface of the lining 11. The overlay 12 is a Bi-Sb alloy plating film, and a Bi-Sb oxide is formed on the surface. The overlay 12 may contain unavoidable impurities. The content of the unavoidable impurities in the overlay 12 is, for example, 0.5 mass % or less in total.

[0020] With the above configuration, for example, a sliding member can be formed by an overlay 12 having a thickness of 8 to 20 μm, an intermediate layer 13 made of Ag-Sn having a thickness of 2 μm, a lining 11 made of a Cu alloy having a thickness of 0.2 mm, and a backing metal 10 having a thickness of 1.5 mm. Also, for example, a sliding member can be formed by an overlay 12 having a thickness of 3 to 10 μm, a second intermediate layer having a thickness of 3 to 6 μm, a first intermediate layer having a thickness of 1 μm, a lining 11 made of an Al alloy having a thickness of 0.3 mm, and a backing metal 10 having a thickness of 1.5 mm.

[0021] (1-2) Manufacturing method of slide member: In this embodiment, Bi-Sb oxide is formed on the surface of the overlay 12. The overlay 12 is formed by oxidizing an alloy plating film of Bi and Sb. Here, an example of a manufacturing method for a slide member will be described taking as an example a configuration in which the lining 11 is a Cu alloy containing Sn, Ni, and Bi, and the intermediate layer 13 is Ag-Sn. In this example of a manufacturing method for a slide member, first, a flat plate of low carbon steel having the same thickness as the back metal 10 is prepared.

[0022] Next, powders of materials constituting the lining 11 are scattered on a flat plate made of low carbon steel. Specifically, for example, powders of Cu, Sn, Ni, and Bi are scattered on the flat plate of low carbon steel so as to obtain the mass ratio of each component in the lining 11 described above. In the lining 11, it is only necessary to satisfy the mass ratio of each component, and alloy powders of Cu-Sn, Cu-Ni, Cu-Bi, etc. may be scattered on the flat plate of low carbon steel. The particle size of the powder may be adjusted to, for example, 150 μm or less using a test sieve (JIS Z8801).

[0023] Next, the low carbon steel flat plate and the powder scattered on the flat plate are sintered. The sintering temperature is controlled to 700 to 1000°C, and sintering is performed in an inert atmosphere. After sintering, the plate is cooled. The lining 11 does not necessarily have to be formed by sintering, and may be formed by casting or the like. When cooling is completed, a Cu alloy layer is formed on the low carbon steel flat plate.

[0024] Next, the low carbon steel on which the Cu alloy layer has been formed is pressed so as to have a shape obtained by dividing a hollow cylinder into two equal parts in the diametrical direction. At this time, the press working is performed so that the outer diameter of the low carbon steel coincides with the outer diameter of the slide member 1.

[0025] Next, the surface of the Cu alloy layer formed on the backing metal 10 is cut. At this time, the cutting amount is controlled so that the thickness of the Cu alloy layer formed on the backing metal 10 is the same as that of the lining 11. As a result, the lining 11 is formed by the Cu alloy layer after cutting. The cutting is performed by a lathe on which a cutting tool material formed of sintered diamond is set, for example.

[0026] Next, Ag and Sn are electroplated on the surface of the lining 11 to a thickness of, for example, 2 μm to form the intermediate layer 13. Here, the concentrations of Ag and Sn formed as the intermediate layer 13 can be adjusted by adjusting the metal ion concentrations in the plating bath.

[0027] Next, Bi and Sb are laminated on the surface of the intermediate layer 13 by electroplating, for example, to a thickness of 8 to 20 μm. The electroplating procedure is, for example, as follows. First, the surface of the intermediate layer 13 is washed with water. Furthermore, the surface of the intermediate layer 13 is pickled to remove unnecessary oxides from the surface of the intermediate layer 13. Thereafter, the surface of the intermediate layer 13 is washed with water again.

[0028] After the above pretreatment is completed, a current is supplied to the lining 11 immersed in the plating bath to perform electroplating. The bath composition is, for example, a plating bath containing 150 g / L of methanesulfonic acid, 20 g / L of bismuth methanesulfonate, and 25 g / L of an organic surfactant. In the above plating bath, pure Sb is dissolved by electrolysis, for example, at 1.0 g / L. The bath temperature of the plating bath is set to 30°C. Furthermore, the current supplied to the lining 11 is a direct current, and the current density is set to 2.0 A / dm 2 It was decided.

[0029] In the plating bath, for example, the methanesulfonic acid can be adjusted between 50 and 250 g / L, the Bi methanesulfonate can be adjusted between 5 and 40 g / L, the amount of Sb dissolved can be adjusted between 0.3 and 1.5 g / L, and the organic surfactant can be adjusted between 0.5 and 50 g / L. The bath temperature of the plating bath can be adjusted between 20 and 50° C., and the current density of the current supplied to the lining 11 can be adjusted between 0.5 and 7.5 A / dm 2 The concentration of Sb in the overlay 12 can be increased by increasing the ion concentration of Sb in the plating bath.

[0030] After electroplating is performed as described above, washing with water and drying are performed. Next, an oxide film is formed on the surface of the overlay 12. There are various methods for forming the oxide film. For example, after electroplating, washing with water and drying, the product is immersed in paraffin oil containing 1000 ppm of organic peroxide (methyl ethyl ketone peroxide, cumene hydroperoxide, etc.) and heated at 150°C for 50 hours as an oxidation treatment. Alternatively, the oxidation treatment may be performed by heating the product after electroplating, washing with water and drying at 200°C for 50 hours in an air atmosphere.

[0031] In addition, when the lining 11 is an Al alloy, for example, the molten material of the lining 11 is poured into a mold, and the molten material of the lining 11 is drawn in the casting direction from an opening of the mold, thereby forming a continuously cast plate of the lining 11. Furthermore, the continuously cast plate of the lining 11 is cold rolled to the thickness of the lining 11. Furthermore, the low carbon steel plate of the back metal 10 is also cold rolled together, thereby forming a rolled plate in which the continuously cast plate of the lining 11 and the low carbon steel plate of the back metal 10 are pressure-bonded together.

[0032] Furthermore, the intermediate layer 13 is formed by electroplating or the like. When the intermediate layer 13 is composed of a first intermediate layer and a second intermediate layer, for example, the first intermediate layer is formed by stacking Cu by electroplating to a thickness of, for example, 1 μm on the surface of the lining 11. Also, the second intermediate layer is formed by stacking Ag or the like by electroplating to a thickness of, for example, 3 to 6 μm on the surface of the first intermediate layer.

[0033] (2) Experimental results: As described above, when an oxide film is formed on the surface of the overlay 12, the slide member 1 is completed. Furthermore, when two slide members 1 are combined into a cylindrical shape, a plain bearing is formed. In the above-described slide member 1, it is sufficient that the overlay 12 contains both Bi and Sb (both greater than 0 mass%), and the Sb concentration is arbitrary. [Table 1] [Table 2]

[0034] Tables 1 and 2 are diagrams showing the main composition of the overlay 12 at each depth for a number of examples and comparative examples with different Sb concentrations (mass concentrations). In Examples 1 to 6 and Comparative Examples 1 to 6 in Table 1, the lining 11 is a 200 μm Cu alloy containing Sn, Ni, and Bi, the intermediate layer 13 is a 2 μm layer of Ag-Sn, and the overlay 12 is a 15 μm layer. In Examples 7 to 12 and Comparative Examples 7 to 12, the lining 11 is a 300 μm Al alloy containing Sn and Si, the intermediate layer 13 is a 4 μm layer of Ag, and the overlay 12 is a 15 μm layer. In Example 13 and Comparative Example 13, the lining 11 is a 300 μm Al alloy containing Sn and Si, the intermediate layer 13 is a 1 μm first intermediate layer of Cu and a 5 μm second intermediate layer of Ag, and the overlay 12 is a 15 μm layer. In addition, while the oxidation treatment was carried out in paraffin oil in the examples, no oxidation treatment was carried out in the comparative examples.

[0035] The Sb concentration is 2.0 mass% to 12.0 mass% in Examples 1 to 6 and Examples 7 to 12, and is also 2.0 mass% to 12.0 mass% in Comparative Examples 1 to 6 and Comparative Examples 7 to 12. The Sb concentration is 5.0 mass% in Example 13 and Comparative Example 13. The Sb concentration in overlay 12 can be adjusted by increasing or decreasing the Sb concentration in the electroplating bath.

[0036] Tables 1 and 2 show the main composition at each depth position from the outermost surface of the overlay 12. That is, the main composition at each depth of 0 μm (outermost surface), 0.01 μm, 0.05 μm, 0.1 μm, 1 μm, and 3 μm of each sample is shown.

[0037] The main composition at each depth position was measured using a scanning X-ray photoelectron spectroscopy analyzer (PHI X-tool manufactured by ULVAC-PHI). That is, measurement regions were set at each position of 0 μm, 0.01 μm, 0.05 μm, 0.1 μm, 1 μm, and 3 μm in the depth direction of the overlay 12, and X-ray photoelectron spectroscopy was performed. The size and shape of the measurement region were square with sides of 2 mm, and the composition present in the measurement region was identified from the binding energy obtained for the measurement region at each depth, and the abundance ratio of each composition was quantified from the peak area ratio. Then, a composition whose abundance ratio was equal to or greater than a threshold was identified as the main composition. The main composition may be defined by various methods, and for example, N compounds (N is an integer equal to or greater than 1) in descending order of abundance ratio may be the main composition. Also, compounds whose abundance ratio is equal to or greater than a threshold and whose abundance ratio is up to the top N may be the main composition. In any case, the compound with the highest abundance ratio is the main composition.

[0038] For example, in all of Examples 1 to 13, the main composition of the outermost surface is Bi-Sb oxide (Bi-Sb-O). In all of Examples 1 to 13, the abundance ratio of Bi-Sb-O compound is greater than that of other compounds and elemental metals at least in the outermost surface. In Examples 1 to 13, Bi-Sb oxide is formed as the main composition over the entire sliding surface between the overlay 12 and the counter shaft 2. On the other hand, in all of Comparative Examples 1 to 13, the main composition of the outermost surface is not oxide.

[0039] Bi-Sb oxide is a very stable compound. Therefore, the presence of Bi-Sb oxide on the outermost surface can protect the overlay 12. Therefore, Examples 1 to 13 in which Bi-Sb oxide is present on the outermost surface have higher fatigue resistance than Comparative Examples 1 to 13 in which Bi-Sb oxide is not present on the outermost surface. In Table 1, the results of the fatigue tests performed on the sliding members of Examples 1 to 13 and Comparative Examples 1 to 13 are shown as fatigue area ratios (%). FIG. 3 is a graph showing the fatigue area ratios (%). In FIG. 3, the horizontal axis represents the Sb concentration in the overlay 12, and Examples 1 to 6 are plotted with black circles, Examples 7 to 12 with black squares, and Example 13 with black triangles. Comparative Examples 1 to 6 are plotted with white circles, Comparative Examples 7 to 12 with white squares, and Comparative Example 13 with white triangles.

[0040] The fatigue area ratio was measured by the following procedure. Figure 2 is an explanatory diagram of the fatigue test. First, as shown in Figure 2, a connecting rod R with cylindrical through holes formed at both ends in the length direction was prepared, and a test shaft H (hatched) was supported by the through hole at one end.

[0041] An overlay 12 (black) similar to that of the sliding member 1 was formed on the inner circumferential surface of the through hole of the connecting rod R that supports the test shaft H. The test shaft H was supported on both outsides of the connecting rod R in the axial direction of the test shaft H, and the test shaft H was rotated so that the sliding speed was 6.6 m / sec. The sliding speed is the relative speed between the surface of the overlay 12 and the test shaft H. The end of the connecting rod R opposite to the test shaft H was connected to a moving body F that reciprocates in the length direction of the connecting rod R, and the reciprocating load of the moving body F was set to 100 MPa. Engine oil at about 140°C was supplied between the connecting rod R and the test shaft H.

[0042] The above state was continued for 100 hours to perform a fatigue test on the overlay 12. After the fatigue test, the inner surface (sliding surface) of the overlay 12 was photographed from a position on a line perpendicular to the surface, with the line as the main optical axis, to obtain an evaluation image, which was the photographed image. Damaged parts of the surface of the overlay 12 shown in the evaluation image were identified by observing with a binocular (magnifying glass), and the area of ​​the damaged parts, which was the area of ​​the damaged parts, was divided by the area of ​​the entire surface of the overlay 12 shown in the evaluation image to measure the fatigue area ratio as a percentage.

[0043] Comparing samples with the same Sb concentration (for example, Example 1 and Comparative Example 1) based on Tables 1, 2 and FIG. 3, it is found that, at all Sb concentrations, the fatigue area ratios of Examples 1 to 6 having Bi-Sb oxide on the outermost surface are smaller than those of Comparative Examples 1 to 6. The fatigue area ratios of Examples 7 to 12 are smaller than those of Comparative Examples 7 to 12. The fatigue area ratio of Example 13 is smaller than that of Comparative Example 13. Therefore, it can be said that the slide member 1 having Bi-Sb oxide has higher fatigue resistance than a slide member not having Bi-Sb oxide.

[0044] Furthermore, when Bi-Sb oxide is present on the outermost surface as in Examples 1 to 13, the possibility of elements present deeper than the outermost surface being oxidized can be reduced, and therefore, bismuth oxide (Bi2O3) can be prevented from being generated as a main component and from growing in the overlay 12.

[0045] That is, since bismuth oxide is brittle, when it is formed on the overlay 12, it may fall off during the use of the sliding member. However, when Bi-Sb oxide is present on the outermost surface as in Examples 1 to 13, it is possible to prevent Bi from being oxidized and generating bismuth oxide in a region deeper than the outermost surface. Therefore, in Examples 1 to 13, it is considered that the prevention of the generation of bismuth oxide also contributes to the improvement of fatigue resistance. In Examples 1 to 13, the Sb concentration is 2.0 mass% to 12.0 mass%, and in any Sb concentration within this concentration range, when Bi-Sb oxide is present on the surface, the fatigue area ratio is smaller than when Bi-Sb oxide is not present. Therefore, it is considered that the formation of Bi-Sb oxide improves fatigue resistance at any Sb concentration in the overlay 12 that is greater than 0 mass%.

[0046] If it is desired to obtain a slide member 1 in which the fatigue-resistant area ratio in the above-mentioned fatigue test falls within a specific range, the Sb concentration in the overlay 12 may be controlled. For example, when it is desired to set the fatigue area ratio to 11% or less, it is preferable to set the Sb concentration in the overlay 12 to 3.0% by mass or more and 10.0% by mass or less.

[0047] Furthermore, in Examples 2 to 6 and Examples 8 to 13, the main composition is Bi-Sb oxide and antimony oxide (Sb2O3) immediately below the layer in which Bi-Sb oxide is the main composition. For example, in Example 2, Bi-Sb oxide exists as the main composition in the surface layer, and at a depth of 0.1 μm immediately below, the main composition is Bi-Sb oxide and antimony oxide (Sb2O3). Then, at a depth of 1 μm, no oxide is observed, and Bi and Sb exist as the main composition. Thus, in Examples 2 to 6 and Examples 8 to 13, oxides other than Bi-Sb-O are also generated at a deep position in the overlay 12. However, since Sb is more easily oxidized than Bi and Sb, antimony oxide is generated more than bismuth oxide. Therefore, the generation of bismuth oxide is suppressed, and bismuth oxide does not exist as the main composition (as the compound with the highest or second highest abundance ratio), and fatigue resistance is improved.

[0048] Therefore, it is possible to prevent the sliding member from becoming brittle due to bismuth oxide. In this way, even if the Sb concentration is low, if a Bi-Sb oxide is formed on the outermost surface, the Bi-Sb oxide protects the surface, thereby preventing the generation of bismuth oxide and improving fatigue resistance. On the other hand, even if an oxidation treatment is performed on a sliding member in which the Sb concentration in the overlay 12 is zero, for example, a sliding member in which the overlay 12 is made of Bi, or made of Bi-Cu, Bi-Sn, etc., and other layers are the same as those in Examples 1 to 13, it is difficult to protect the outermost surface with an oxide.

[0049] That is, when the overlay 12 not containing Sb is subjected to an oxidation treatment, bismuth oxide (Bi2O3) is formed on the outermost surface. When the above-mentioned fatigue test is performed on a sample with bismuth oxide formed on the outermost surface, a fatigue area ratio exceeding 20% ​​is obtained. That is, the sliding member with bismuth oxide formed on the outermost surface has lower fatigue resistance compared to the examples due to reasons such as the brittle bismuth oxide falling off. In the examples, Bi-Sb oxide is formed on the outermost surface, which suppresses the generation of bismuth oxide and the falling off of bismuth oxide. Therefore, Bi is maintained in the overlay 12 for a long period of time, and the high compatibility due to soft Bi can be self-sufficient for a long period of time.

[0050] The intermediate layer 13 and the lining 11 are different between Examples 1 to 6, Examples 7 to 12, and Example 13. That is, the intermediate layer 13 in Examples 1 to 6 is made of Ag-Sn. The intermediate layer 13 in Examples 7 to 12 is made of Ag. The intermediate layer in Example 13 is made of a first intermediate layer (Cu) and a second intermediate layer (Ag). Comparing these Examples, the main composition of the overlay 12 is the same, and the fatigue area ratio is also very close. Furthermore, compared to Comparative Examples 1 to 6, Comparative Examples 7 to 12, and Comparative Example 13, the fatigue resistant area is smaller in the Examples. Therefore, it is considered that the improvement in the fatigue resistant area by forming a Bi-Sb oxide on the outermost surface of the overlay 12 made of Bi and Sb can be achieved regardless of the composition of the intermediate layer 13 and the lining 11.

[0051] The main composition at each depth position from the outermost surface shown in Table 1 is the result of measuring the slide member before the fatigue test. Meanwhile, the main composition was also measured after the fatigue test. As a result, no change was observed in the main composition at each depth position in both Examples 1 to 13 and Comparative Examples 1 to 13. That is, in the outermost surface of Comparative Examples 1 to 13, oxide was not formed as the main composition even after the fatigue test. Therefore, in a state where oxidation treatment is not actively performed as in Comparative Examples 1 to 13, it is difficult to form Bi-Sb oxide uniformly over the entire surface of the outermost surface during normal use of the slide member 1. Meanwhile, when oxidation treatment is actively performed as in Examples 1 to 13, Bi-Sb oxide is formed uniformly over the entire surface of the outermost surface.

[0052] In Comparative Examples 1 to 13, even if Bi-Sb oxide is unlikely to form on the outermost surface during normal use, Bi may be locally oxidized to generate bismuth oxide because Bi-Sb oxide is not formed on the outermost surface in these Comparative Examples 1 to 13. When bismuth oxide is generated, the bismuth oxide is brittle, and the fatigue resistance decreases due to the bismuth oxide falling off, etc. Therefore, as in Examples 1 to 13, by performing a pre-oxidation treatment to form Bi-Sb oxide over the entire outermost surface, the fatigue resistance can be reliably improved.

[0053] (3) Other embodiments: In the above embodiment, the sliding member 1 constituting the sliding bearing A for bearing the crankshaft of the engine has been exemplified, but the sliding member 1 of the present invention may be used to form a sliding bearing A for other applications. For example, the sliding member 1 of the present invention may be used to form radial bearings such as gear bushings for transmissions, piston pin bushings, boss bushings, etc. Furthermore, the sliding member of the present invention may be a thrust bearing, various washers, or a swash plate for a compressor of an automobile air conditioner.

[0054] Furthermore, the matrix of the lining 11 is not limited to a Cu alloy or an Al alloy, and the material of the matrix may be selected depending on the hardness of the mating shaft 2. Furthermore, the back metal 10 is not essential and may be omitted. [Explanation of symbols]

[0055] Reference Signs List 1: sliding member, 2: mating shaft, 10: backing metal, 11: lining, 12: overlay, 13: intermediate layer, A: bearing, F: moving body, H: test shaft, R: connecting rod

Claims

1. A sliding member having an overlay formed of a Bi and Sb alloy plating film, A Bi—Sb oxide is formed on the surface of the overlay before use. Sliding member.

2. The Sb concentration in the overlay is 2.0% by mass or more and 12.0% by mass or less. The sliding member according to claim 1 .

3. The Sb concentration in the overlay is 3.0% by mass or more and 10.0% by mass or less. The sliding member according to claim 1 .

4. In the depth direction of the overlay, antimony oxide is formed directly below the Bi—Sb oxide. The sliding member according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Article drive controller

    JP1985087684A

  • Sliding member and manufacturing method of the same

    JP2014185378A

  • Sliding member

    WO2019198369A1